PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS KETAHANAN PANGAN, PERTANIAN DAN PERIKANAN KOTA METRO LAMPUNG - Nurmalina, Nurmalina; Mazni, Afdal; Dacholfany, Muhammad Ihsan (SIMPLEX: Journal of Economic Management, 2024)
The food, agriculture, and fisheries security service of Metro City, Lampung, in carrying out work following mayor regulation Number 39 of 2019 concerning the third amendment to Metro City Mayor Regulation Number 31 of 2016 concerning the composition, duties, and functions of the Metro City Regional apparatus and also refers to standard operating procedures (SOP). Also, employee performance will increase if supported by a conducive work environment and a leader who consistentlymotivates employees. The formulation of the problem in this study is 1) Is there any influence of leadership on employees' performance at the Food Security, Agriculture and Fisheries Office of Metro City, Lampung? 2) Is there any influence of the work environment on employees' performance at the Department of Food Security, Agriculture and Fisheries, Metro City, Lampung? 3) Is there a joint influence of discipline and work environment on employees' performance at the Food Security, Agriculture and Fisheries Service Office of Metro City, Lampung?This research was conducted at the Department of Food Security, Agriculture, and Fisheries, Metro City, Lampung. The sampling technique used proportional random sampling to 50 respondents, namely the Department of Food Security, Agriculture and Fisheries, Metro City, Lampung. The analysis technique in this research is using a multiple linear regression test. From the study results, it can be concluded that leadership and work environment influence employee performance partially or simultaneously. This shows that employees who are motivated by the leader will affect the way they work and result in increased performance. Also, a conducive work environment supports employees to improve their performance to produce optimal performance in carrying out tasks and jobs on time.